PENGARUH MODEL PROJECT BASED LEARNING TERHADAP SELF EFFICACY SISWA PADA PELAJARAN MATEMATIKA KELAS IV SD INPRES PABANGIANG - Nurlianti; Sirajuddin; Rezki Ramdani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on the lack of student self-efficacy in mathematics lessons. Students find mathematics learning difficult so they lack confidence in solving mathematical problems. One solution to this problem is the implementation of the Project Based Learning model. This learning model helps students develop thinking skills, collaborate, and practice to solve problems that will ultimately improve student self-efficacy. This study aims to determine the effect of the Project Based Learning model on student self-efficacy in mathematics lessons in grade IV of SD Inpres Pabangiang. This research is an experimental study with a pre-experimental one group design. The sample in this study was 24 students. Data collection techniques used the results of distributing questionnaires, observation sheets, and test sheets. Data analysis techniques used descriptive statistical analysis techniques and inferential analysis techniques. The results in this study indicate a significant effect on the application of the Project Based Learning model on student self-efficacy. This can be seen from the average results of the initial and final self-efficacy questionnaires. The average initial self-efficacy score for students was 77, which is considered low, and the average final self-efficacy score for students was 91, which is considered very high. Furthermore, the normality test results showed that all data were normally distributed, with all significance values ​​> 0.05, and the t-test results also showed a significance value of 0.000 < 0.05. Therefore, it was concluded that H0 was rejected and H1 was accepted, indicating a significant effect of the implementation of the Project-Based Learning model on students' self-efficacy in mathematics.